Acceptability of the proposed crematorium to the residents of Iloilo City - Dabi, Shallemar; Daynolo, Marite; Grafil, Jazzel; Guanco, Schenley Marie; Lujan, Marian (2007.)
This study aimed to determine the level of acceptability of the residents of Iloilo City to the proposed establishment of crematorium. It likewise aimed to ascertain whether (1) socio-demographic factors such as age, sex, civil status, years of residency and average monthly income as well as economic status influence the acceptability of the residents of Iloilo City to the construction of crematorium; (2) customs, traditions and religious beliefs affects the acceptability of the residents of Iloilo City to the construction of crematorium, (3) the knowledge of the respondents about what the cremation process is influence their acceptability of the construction of crematorium and (4) environmental concerns such as health of the residents in the vicinity and air pollution affect the acceptability of the residents of Iloilo City to the construction of crematorium. This descriptive research utilized a researcher-made questionnaire. There were 100 respondents from Iloilo City. The data gathered for this study were subjected to certain computer processed statistics. For descriptive analysis, frequency count was used while the mean and chi square at .05 level of significant difference were employed as the inferential statistics. All statistical computations were done through the use of Statistical Package for Social science or SPSS. The results of the study showed that the residents of Iloilo did not accept the proposed establishment of crematorium because of various reasons. The years of residency, preferred burial practice and environmental problems that are believed to result affect their level of acceptability of the proposed construction of crematorium. The results of the study revealed that variable that mainly influenced the level of acceptability of the residents was the environmental considerations particularly air pollution and other factors that are detrimental to the health of the rsidents. With all these considerations, the findings of the study on the level of acceptability of the proposed construction of crematorium among the resients of Iloilo City showed that it was acceptable among the respondents considering their socio-demographic characteristics, customs and traditions, religious beliefs and their knowledge on cremation. Only the years of residency, environmental factors and burial preference had an effect on the level of acceptability.
Research Paper (BA 199-Business Research) -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 2007.